2022
DOI: 10.1155/2022/1864169
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on the Mechanical Characteristics of Natural Fiber Particle‐Reinforced Polymer Composites under Cryogenic Environment

Abstract: In the past few years, researchers have turned away from previous metals and minerals and more towards lightweight materials throughout addition to creating lightweight, better effective composites for special tasks. The composite materials were created by employing the most advantageous hand layup approach. To attain the aforementioned goals, the following limitations were implemented: at various levels, (i) coconut shell powder, (ii) walnut powder, and (iii) cryogenic treatment hours are all accessible. At 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The 80 μm particle size exhibited enhanced dispersion quality in the matrix due to increased interaction at the boundary surface. 25 Although, there are many reports related to the reinforcement of natural filler into polymeric matrix, this is a unique natural filler, not explored before. Most studies are restricted to packaging applications or for antioxidant and antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 80 μm particle size exhibited enhanced dispersion quality in the matrix due to increased interaction at the boundary surface. 25 Although, there are many reports related to the reinforcement of natural filler into polymeric matrix, this is a unique natural filler, not explored before. Most studies are restricted to packaging applications or for antioxidant and antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…SEM images showed that due to the reduction in the size of the filler, better interface bonding was achieved between the filler and matrix, thus improving the mechanical strength. The 80 μm particle size exhibited enhanced dispersion quality in the matrix due to increased interaction at the boundary surface 25 …”
Section: Introductionmentioning
confidence: 99%